A 12-Year Experience With Chimney and Periscope Grafts for Treatment of Type I Endoleaks. (August 2015) - Montelione, Nunzio; Pecoraro, Felice; Puippe, Gilbert; Chaykovska, Lyubov; Rancic, Zoran; Pfammatter, Thomas; Mayer, Dieter; Amann-Vesti, Beatrice; Husmann, Marc J.; Veith, Frank J.; Mangialardi, Nicola; Lachat, Mario
Purpose : To evaluate the midterm outcomes of chimney and/or periscope grafts (CPGs) in patients presenting type I endoleak after a previous endovascular aneurysm repair (EVAR).Methods: Between June 2002 and April 2014, 24 consecutive patients (mean age 73.9±9.2 years; 23 men) presenting a type I endoleak were addressed with CPGs to extend the proximal and/or distal landing zone and to maintain side branch perfusion. Indication for treatment was a type Ia endoleak in 23 (96%) patients and a type Ib endoleak in one. Median interval from the previous EVAR to endoleak treatment with CPGs was 52.2±48.9 months (range 0.2–179). All patients had proximal/distal landing zones precluding any standard endovascular reintervention. Measured outcomes included technical success and perioperative mortality and morbidity. Technical success was defined as a procedure completed as intended, with no secondary procedures within 30 days. Midterm outcomes included survival, CPG patency, endoleaks, and freedom from reintervention.Results: Technical success was 96%; a single patient required an additional procedure to seal a recurrent type Ia endoleak. Intraoperative revascularization of all 55 target vessels (2.3/patient) with CPGs was successful. One (4%) patient died within 30 days. Estimated survival at 12, 24, and 36 months was 83%; estimated CPG patency at the same intervals was 94%. Over a mean follow-up of 23.4±29 months, 6 (25%) reinterventions were performed; of these, 4 were secondary to type I endoleak. Aneurysm diameters reduced from 88.3±26 to 85.5±33 mm (p=0.49) over the mean follow-up.Conclusion: The CPG technique is a safe and effective tool for treatment of type I endoleak after previous EVAR. The CPG technique is feasible even in nonelective patients, with excellent outcomes in terms of patency. Close imaging follow-up is warranted to rule out recurrent or de novo endoleaks.